HUBUNGAN FAKTOR DEMOGRAFI DAN PERILAKU SEKSUAL TERHADAP KEJADIAN INFEKSI MENULAR SEKSUAL PADA WANITA PEKERJA SEKS - Yuli Fitriasih; Yuli Fitriasih; Nurhalim Shahib; farid Husin (Universitas Harapan Bangsa Purwokerto, 2018)
Abstract Sexually transmitted infections are infections that can be spread through vaginal, anal or oral. Female sex workers particularly at risk for sexually transmitted infections. Preliminary studies in Cilacap district STI clinic in 2011 showed that the incidence of sexually transmitted infections is still quite high (60.81%). Complex causal factors cause the difficulty of breaking the chain of IMS. This study aims to analyze the relationship between demographic factors and high-risk sexual behavior of high risk on the incidence of sexually transmitted infections and the risk factors on the incidence of sexually transmitted infections in female sex workers. Analytic survey research through case-control study (case-control) with a total sampling on 70 female sex workers in brothels Slarang conducted during the month of November 2013. Questionnaire as a means of collecting research data. Univariate analysis to determine the frequency distribution of incidence of STIs. Bivariate analysis using contingency coefficient test. Multivariate analysis using logistic regression. The results showed that there is a significant association between the incidence of STIs in high- risk demographic factors with r value (0.239) and p-value (0.040), there is a significant association between the incidence of STIs in high- risk sexual behavior factors with values ​​of r (0.307; 0.230) and the p-value ( 0.007; 0.048) respectively. Multivariate analysis showed that condom use is not routine is that most risk factors on the incidence of sexually transmitted infections in female sex workers with OR value 5.835. Conclusions of the study: female sex workers who do not regularly use condoms have 5.835 times greater risk for sexually transmitted infections. A total of 65% the proportion of female sex workers suffer preventable sexually transmitted infection, if condom use. Keywords : female sex workers, demographic factors, sexual behavior factors, sexually transmitted infections